Strategies for Empowering Small and Medium Enterprises to Promote Sustainable Tourism in Tourist Villages: A Systematic Literature Review - Zahro, Yosabah; Hartiningsih, Sri (Global Economic, Social, and Development Review, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial drivers of sustainable tourism in rural communities, yet their potential is often constrained by structural challenges. This systematic literature review, conducted using the PRISMA protocol covering publications from 2020 to 2025, analyzes empowerment strategies for MSMEs in tourism villages, focusing on Indonesia and the Philippines. The findings reveal that leadership, digital innovation, and capacity development are essential for strengthening economic resilience, environmental preservation, and cultural conservation. Successful cases, such as Ponggok Village (Indonesia) demonstrate how an integrated approach—combining stakeholder collaboration, technology, and training—can enhance operational efficiency and expand market access. However, barriers such as uneven infrastructure, low digital literacy, and dependence on external funding persist, necessitating local policy interventions. This study underscores the need for inclusive governance models that prioritize marginalized groups (e.g., women and rural entrepreneurs) and align with the UN Sustainable Development Goals (SDGs 8, 9, and 11). The limitations of this research include its geographical focus on Southeast Asia and the predominance of short-term case studies. Future research should explore long-term impacts and develop measurable frameworks applicable to diverse socio-economic contexts. This paper contributes to the discourse on inclusive tourism development by providing actionable insights for policymakers, practitioners, and academics to leverage MSMEs as catalysts for sustainable rural transformation.